Mutational analysis of the NPHS2 gene in Czech patients with idiopathic nephrotic syndrome - Reiterová, J; Safránková, H; Obeidová, L; Stěkrová, J; Maixnerová, D; Merta, M; Tesař, V (Folia biologica, 2012)
Focal segmental glomerulosclerosis and minimal change disease represent frequent histological patterns of renal injury in patients with nephrotic syndrome. Few cases carrying NPHS2 gene variants have been described to date. Mutational analysis of the NPHS2 gene was performed in 50 Czech adult patients with histologically proved FSGS/MCD. The common p.P20L and p.R229Q polymorphisms of the NPHS2 gene were tested in 169 patients with IgA nephropathy and in 300 individuals of the control group. No mutation in the NPHS2 gene in patients with adult onset was identified. One homozygous mutation p.V290M in a patient with onset in early childhood was found. One new heterozygous variant in the non-conservative area of the NPHS2 gene, p.G97S, was identified in a patient with childhood-onset FSGS. In one adult patient, there were two polymorphisms, p.P20L and p.R229Q, in trans-heterozygous state, which could contribute to steroid-resistant nephrotic syndrome. The most common polymorphism p.R229Q was identified in 12 % of FSGS/ MCD patients, in 11.8 % of IGAN patients and in 10% of controls. The heterozygosity of p.R229Q polymorphism was similar in the IGAN group, with non-significantly higher prevalence in IGAN patients with progressive form of the disease (15.9 % versus 9.4 %). The prevalence of p.P20L polymorphism was not significantly different among the groups (6 % in FSGS patients, 1.8 % in IGAN patients, 1 % in the control group). To conclude, NPHS2 mutations are rare in patients with adult onset of FSGS/MCD. The R229Q polymorphism is frequent in the Czech population and probably could have some influence on IGAN.
Keywords: mutace; dospělí; Female; Prevalence; IgA nefropatie; Adult; homozygot; nefrotický syndrom; ženské pohlaví; mutační analýza DNA; Nephrotic Syndrome; lidé; intracelulární signální peptidy a proteiny; DNA Mutational Analysis; membránové proteiny; genetická predispozice k nemoci; Mutation; Genetic Predisposition to Disease; Homozygote; prevalence; Male; Czech Republic; Intracellular Signaling Peptides and Proteins; polymorfismus genetický; Membrane Proteins; Česká republika; lidé středního věku; mužské pohlaví; Polymorphism, Genetic; Middle Aged; Glomerulonephritis, IGA; Humans